"Three had a passion for agriculture, and no good was found in them": God and soil in "Genesis Rabbah" - Proefrock, Rebecca C. (Biblische Notizen, 2010)
In Bereshit Rabbah we read, “Three had a passion for agriculture, and no good was found in them: Cain, Noah, and Uzziah.” Is this an expression of the supposedly „anti-farming“ attitude of the Jews? The article shows that this is due less to the prejudice of the rabbinical writers than to their care not to mix God with the earth. There is a limit of ecological consciousness.